Emocjonalność a obrazowość polszczyzny średniowiecznej i ich tekstowe aktualizacje - Rejter, Artur (Stylistyka, 2021)
The work provides an analysis of the relations between emotionality and picturesque[1]ness of Medieval Polish. This refers to both emotionality expressed by language or textual means, the sender’s attitude and the intention of the message regarding the assumed receiver. The picturesqueness, being a semantic feature of the Old-Polish language, yet also understood in the category of stylistic shaping of the text, remains here in the relation of complementarity and should be considered jointly with refer[1]ence to the emotional markedness of the utterance and its manifestations.